(untitled) ("Conference on Universal Science Research 2023", 2025)
Embroidery and gold embellishment (zardozi) are among the most cherished forms of traditional craftsmanship in Central Asia, particularly in Uzbekistan. These intricate textile arts, often passed down through generations in family settings or artisan schools, serve not only as decorative techniques but also as carriers of historical memory, regional identity, and spiritual symbolism